2012
DOI: 10.1016/j.cub.2012.07.035
|View full text |Cite
|
Sign up to set email alerts
|

A Potentially Fatal Mix of Herpes in Zoos

Abstract: Pathogens often have a limited host range, but some can opportunistically jump to new species. Anthropogenic activities that mix reservoir species with novel, hence susceptible, species can provide opportunities for pathogens to spread beyond their normal host range. Furthermore, rapid evolution can produce new pathogens by mechanisms such as genetic recombination. Zoos unintentionally provide pathogens with a high diversity of species from different continents and habitats assembled within a confined space. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 30 publications
(41 reference statements)
1
62
0
3
Order By: Relevance
“…These findings are not completely unexpected since such natural interspecies recombination events have already been documented in other mammalian herpesviruses (equine herpesviruses; Pagamjav et al 2005; Greenwood et al 2012). What may be more surprising is that recombination within HSV-1 and HSV-2 has often been investigated and detected during the last decade (for a complete review on recombination in alphaherpesviruses, see Loncoman et al 2016).…”
Section: Discussionsupporting
confidence: 71%
“…These findings are not completely unexpected since such natural interspecies recombination events have already been documented in other mammalian herpesviruses (equine herpesviruses; Pagamjav et al 2005; Greenwood et al 2012). What may be more surprising is that recombination within HSV-1 and HSV-2 has often been investigated and detected during the last decade (for a complete review on recombination in alphaherpesviruses, see Loncoman et al 2016).…”
Section: Discussionsupporting
confidence: 71%
“…As this study has demonstrated EHV-1 to be stable under different environmental water conditions, the water sources would provide EHV-1 with the opportunity to infect potential hosts sharing the water source. This in turn may account for the recent reports of EHV-1-like viruses detected in non-equid species in captivity, as water is a potential transmission conduit for the virus between different species456789.…”
Section: Discussionmentioning
confidence: 83%
“…Although horses are natural hosts for equine herpesviruses, several viruses have recently been discovered that are closely related to EHV-1 and were isolated from both captive and wild animals, including Thompson’s gazelles ( Eudorcas thomsoni )4, Ilamas ( Lama glama )5, alpacas ( Vicugna pacos )6, black bears ( Ursus americanus) , polar bears ( Ursus maritimus )7 and rhinos ( Rhinoceros unicornis )89. Serological and genetic evidence suggests that zebra-conspecific and rhinos in Africa are frequently exposed to EHV-1 and its close relative EHV-9, which may even reservoir in rhinos (Abdelgawad et al .…”
mentioning
confidence: 99%
“…Canine distemper is reported to have caused the death of three neonate polar bears and a spectacled bear at a European zoo. 22 Immunohistochemistry with a polyclonal antibody reactive to several equine herpesviruses was positive within the affected areas of the brain and a polymerase chain reaction (PCR) test conclusively demonstrated the presence of only EHV-9. 29 Equine herpesvirus 9 (EHV-9) was identified in a captive polar bear with a progressive encephalitis with the source being traced to Grevy' s zebras, a potential equid reservoir species.…”
Section: Infectious Diseasesmentioning
confidence: 94%